Alteração no metaboloma e na expressão gênica na via da biossíntese de piranocumarinas em Citrus sinensis x Citrus limonia em resposta ao Huanglongbing - Amaral, Jéssica Cristina (Universidade Federal de São Carlos, 2023)
Greening (Huanglongbing/HLB) is the most destructive citrus disease. It is caused by the bacterium Candidatus Liberibacter asiaticus (CLas), C. Liberibacter africanus and C. Liberibacter americanus and it is transmited by the insect vector psyllid Diaphorina citri. There is no commercial variety of crown plant or rootstock resistant to disease and contaminated plants cannot be cured. Despite of considerable research, there is little knowledge about the processes involved in plant infection and colonization by CL. A study of the plant/bacteria interaction CLas was developed by LC-HRMS/qTOF in positive and negative ionization modes. Central and lateral roots of healthy and CLas-infected plants of C. sinensis x C. limonia cultivated in a greenhouse, and the roots of healthy and infected C. sinensis seedlings cultivated in vitro were analyzed. Through the analysis of the molecular network, it was possible to observe an increase in the concentration of some metabolites in plants infected with HLB. Significant differences using the paired two sample t-test were observed in the concentration of demethylsuberosin, osthenol, 5-methoxyseselin, xanthylethin, seselin and limonin for plants grown in a greenhouse and for xanthylethin, seselin and limonin in seedlings grown in vitro. The compounds mentioned above, were responsible for the classification observed in the PCA analysis, that classified the samples in four groups: roots, lateral roots, lateral roots of health plants and lateral roots of infected plants. The quantification of the expression of DXR, DXS2, PT1 and PT2 genes was carried out by qPCR, in C. sinensis x C. limonia roots of healthy and symptomatic plants infected with CLas. There was a decrease in the expression of the DXR, DXS2 and PT1 genes in plants infected with CLas compared to healthy ones. For DXR, a two-fold decrease in gene expression was observed, for DXS2 by 5.7-fold and for PT1 by 3.6-fold. For the PT2 gene, there was an increase in relative expression for infected plants compared to healthy ones of 2.6 times. These results show that the plant responds by producing some metabolites in greater or lesser quantities in the presence of CLas bacteria, in addition to causing changes in gene expression in the pyranocoumarin biosynthesis pathway. Therefore, a plant reaction is observed inhibiting the biosynthesis of linear coumarin derivatives in favor of angular ones, which are prenylated at C-8.
Variation in metabolome and gene expression of the pyranocoumarins biosynthesis pathway in Citrus sinensis x Citrus limonia in response to Huanglongbing
Keywords: Citrus; Expressão Gênica; Biossíntese; Biossíntese; Piranocumarinas; Preniltransferases; GNPS; Metabolômica; CIENCIAS EXATAS E DA TERRA::QUIMICA